Climate change and the permafrost carbon feedback - Schuur, E.A.G.; McGuire, A.D.; Schädel, C.; Grosse, G.; Harden, J. W.; Hayes, D.J.; Hugelius, G.; Koven, C. D.; Kuhry, P.; Lawrence, D.M.; Natali, S.M.; Olefeldt, D.; et al. (Nature, 2015)
Large quantities of organic carbon are stored in frozen soils (permafrost) within Arctic and sub-Arctic regions. A warming climate can induce environmental changes that accelerate the microbial breakdown of organic carbon and the release of the greenhouse gases carbon dioxide and methane. This feedback can accelerate climate change, but the magnitude and timing of greenhouse gas emission from these regions and their impact on climate change remain uncertain. Here we find that current evidence suggests a gradual and prolonged release of greenhouse gas emissions in a warming climate and present a research strategy with which to target poorly understood aspects of permafrost carbon dynamics.